Critique of Microcredit as a Development Model - Grace Levin (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
The field of microcredit (otherwise known as microfinance, microlending, or microcapital) has expanded rapidly since the 1980s as an economic means of lifting people out of poverty. Generally, microcredit has been accepted as an effective method for empowering both individuals and communities. In recent years, however, critics have brought to light some of the problems associated with microlending, such as the complex socioeconomic factors that can cause loan programs to fail. These problems stem from the basic tenet of microfinance: the need for lending programs to be managed locally in order to understand the needs of a community and assess the sustainability of each project. Lending programs vary a great deal around the world due to cultural differences, and the success of each must be evaluated in a geographic context. The industry of microfinance cannot be standardized due to these vitally important differences, and there are few organizations which have the ability to watch over the practices of individual lenders. As a result, microfinance institutions are largely free to practice autonomously; this independence is vital to the success of each project but also creates a void of authority.
Keywords: Microcredit; Finance; Geography